A saúde de uma comunidade escolar pública do município de Santa Maria de Jetibá-ES: um estudo sobre a esquistossomose - Buss, Glauciomar (2019)
Schistosomiasis is one of the main aquatic parasitic diseases of world. With the evacuation of population from countryside to urban centres, great amount of people started to live in reduced spaces (vilas, favelas, comunidades cariocas) at the periphery of big cities, in a social structure similar of colonial Brazil ages. As strategies destinated to control Schistosomiasis, we can cite: detection and mapping of intermediate host and the places where it occurs. The transmission of the disease is endemic in 47 of 78 cities of Espirito Santo state. Santa Maria do Jetibá city was a settlement colony founded by Emperor Pedro II from Brazil. Their objectives were the reconstruction of Brazilian social space. Whatever, by reasons investigated at this work, the poor sanity and environmental degradation creates opportunities for the appearance of schistosomiasis. Moreover, it was observed citizen reinfected themselves to receive governamental care and aid. Based on this questions, the present work performed a ethnographic-like research (trabalho do tipo etnográfico) in the community of EEEFM Frederico Boldt school. The specific objectives were: identify potencial sites of Schistosomiasis dissemination and educate students about Healthy public political knowledge. It was developed a bilingual didactic material, in Portuguese and Pomerano to educate how to avoid Schistosomiasis, and also, it was performed an educational research and an educational action (pesquisa-ação) with the objective to capacity students as educators agents to teaching community how to avoid Schistosomiasis. Based on this, we hope that students teach population of places with the presence of intermediate host and communicated the school and the government to make the control of Schistosomiasis. During the thesis construction, it was philosophed that water and sanity are the main profilaxia of Schistosomiasis. By this way, it was produced a series of pocket books about water and sanity in shelters of Latin American, based on UNESCO orientations for sustainable development. The volume is about how to avoid Schistosomiasis at Santa Maria do Jetibá, em Portuguese and German, in the way spoked by Santa Maria do Jetibá citizen, an almost extant Europe language from Germany/Poland region. At educational research and educational action the main results were: diagnostic research of previous students knowledgment about Schistosomiasis, participation of students in Science Fair Competition, and the win of second place with science work about Water, course of formation of educators agents to teach scholar community how avoid Schistosomiasis. Students understood very well Schistosomiasis information. A quiz were performed a week after classes and the number of rights answers were higher if compared with quiz of diagnostic evaluation. Moreover, educational practices were successful and students could dialogue very well theory and practice. A lot of students commented data from lectures and classes in school environment